2019
DOI: 10.3390/en12061110
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Renewable Energy System Based on IREOM Model and Spatial–Temporal Series for Isolated Rural Areas in the Region of Valparaiso, Chile

Abstract: Providing energy to areas isolated from the electricity grid through the use of a smart integrated renewable energy system (SIRES) is proposed in this study for Valparaiso, Chile. The study analyzes the process of identifying the appropriate size of a SIRES considering technical and economic factors. An optimization model proposed in the literature was modified, and a subsequent spatial–temporal analysis of the different variables was conducted. The model comprises locally available renewable energy resources,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In developing countries, such as Chile, it is common to find this type of small towns or villages outside the electricity grid. In a study proposed by [9], these villages can be connected or energized by establishing a point of energy center and establishing a distribution line that clusters to all houses. Given the local conditions of the territory and the availability of the permit, the renewable resources can be integrated with solar energy, oil and other units of energy conversion (e.g., biomass gasifiers and agricultural residues), similar to the one presented in the paper of [47].…”
Section: Model Design (Sires)mentioning
confidence: 99%
See 4 more Smart Citations
“…In developing countries, such as Chile, it is common to find this type of small towns or villages outside the electricity grid. In a study proposed by [9], these villages can be connected or energized by establishing a point of energy center and establishing a distribution line that clusters to all houses. Given the local conditions of the territory and the availability of the permit, the renewable resources can be integrated with solar energy, oil and other units of energy conversion (e.g., biomass gasifiers and agricultural residues), similar to the one presented in the paper of [47].…”
Section: Model Design (Sires)mentioning
confidence: 99%
“…Specifically in the Valparaíso region, it was reported that rural towns were located outside the electricity grid, and approximately 735 rural households in this region are without electricity. The work proposed in [9], shows an evaluation summary oriented towards the resources, load, and demand in different villages of the region of Valparaíso. It is observable that the highest average energy contribution is the village of "La Mora" (https://goo.gl/maps/AJpQvPHsgmZKoHX26), located 15 km from "Cabildo" and with 34 off-grid houses, where the main energy source to produce electricity consists of a diesel generator.…”
Section: Case Study For Off-grid Region In Valparaísomentioning
confidence: 99%
See 3 more Smart Citations